2018
DOI: 10.3390/nano8020095
|View full text |Cite
|
Sign up to set email alerts
|

TiO2, SiO2 and ZrO2 Nanoparticles Synergistically Provoke Cellular Oxidative Damage in Freshwater Microalgae

Abstract: Metal-based nanoparticles (NPs) are the most widely used engineered nanomaterials. The individual toxicities of metal-based NPs have been plentifully studied. However, the mixture toxicity of multiple NP systems (n ≥ 3) remains much less understood. Herein, the toxicity of titanium dioxide (TiO2) nanoparticles (NPs), silicon dioxide (SiO2) NPs and zirconium dioxide (ZrO2) NPs to unicellular freshwater algae Scenedesmus obliquus was investigated individually and in binary and ternary combination. Results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…4a). Similarly, it was described that SiO 2 did not have any impact on membrane integrity of algal cells Scenedesmus obliquus (Liu et al 2018). Although it was reported the disruption of cell membrane in yeasts exposed to Al 2 O 3 NPs (Garcia-Saucedo et al 2011) or Mn 2 O 3 (Otero-Gonzalez et al 2013), both results were observed in the presence of 1 g/L NPs, which corresponded to a concentration ten times higher than the one used in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…4a). Similarly, it was described that SiO 2 did not have any impact on membrane integrity of algal cells Scenedesmus obliquus (Liu et al 2018). Although it was reported the disruption of cell membrane in yeasts exposed to Al 2 O 3 NPs (Garcia-Saucedo et al 2011) or Mn 2 O 3 (Otero-Gonzalez et al 2013), both results were observed in the presence of 1 g/L NPs, which corresponded to a concentration ten times higher than the one used in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…3B). A similar result was observed with the alga Scenedesmus obliquus when exposed to SiO 2 NPs (Liu et al, 2018). In relation to protein oxidation, different mechanisms were described, which includes the oxidation of amino acid residues containing aromatic side chain or sulfhydryl groups (Cecarini et al, 2007).…”
Section: )supporting
confidence: 74%
“…Antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST) and peroxidase (POD), among other enzymes, are mechanisms of antioxidant protection in algal cells. In the presence of less toxic NPs, the activity of these antioxidant enzymes increases to eliminate the toxicity of ROS to algal cells [63], and when the toxicity of NPs in water is too strong, the antioxidant defense system of algae cells is destroyed and the enzyme activity is significantly inhibited [45,64].…”
Section: Effect Of Nps On Intracellular Substratesmentioning
confidence: 99%